2015
DOI: 10.1002/phar.1664
|View full text |Cite
|
Sign up to set email alerts
|

Disopyramide for Hypertrophic Cardiomyopathy: A Pragmatic Reappraisal of an Old Drug

Abstract: Hypertrophic cardiomyopathy (HCM) is a genetic cardiac disorder characterized by unexplained left ventricular hypertrophy in the absence of other cardiac or systemic etiologies. Approximately two-thirds of patients with HCM develop left ventricular outflow tract (LVOT) obstruction with or without provocation, whereas nearly half develop heart failure with preserved ejection fraction. Medical management of heart failure with preserved ejection fraction is based on the presence of symptoms and LVOT obstruction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…It is recommended to consider adding disopyramide to a beta blocker or verapamil therapy to treat angina or dyspnea if there is no response to these treatments alone. This should be avoided in patients with reduced systolic function [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to consider adding disopyramide to a beta blocker or verapamil therapy to treat angina or dyspnea if there is no response to these treatments alone. This should be avoided in patients with reduced systolic function [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is a sodium channel blocker with negative inotropic properties that effectively reduces left ventricular outflow tract gradients in adults with HCM [8]. Patients with HCM who are persistently symptomatic despite the use of β-blockers or verapamil and have evidence of LVOT obstruction are prescribed disopyramide [7]. Disopyramide could improve LV diastolic dysfunction in patients with hypertrophic nonobstructive cardiomyopathy (HNCM) [9].…”
Section: Discussionmentioning
confidence: 99%
“…The strong negative inotropic effect of disopyramide prompted its use for the treatment of symptomatic HCM associated with LVOTO [ 35 ]. In 1988, a study involving seven oHCM patients by Sherrid and co-workers reported a solid reduction of the LVOT gradient and an amelioration of diastolic function exerted by disopyramide [ 36 ].…”
Section: Non-selective Drugs To Reduce Symptoms and Prevent Lethal Ar...mentioning
confidence: 99%
“…The need for hospital admission to monitor for potential arrhythmogenicity may disrupt training or competition schedules. [ 79 ] As a result of this potential side effect, guidelines recommend concomitant use of an atrioventricular nodal-blocking agent [ 2 ••].…”
Section: Treatmentmentioning
confidence: 99%